Touching the writing. The body in Henri Michaux’s graphical work and ’Saisir’s’ case for a ’rhetoric of the stroke’ - Romero González, Arantxa (Escritura e Imagen, 2019)
The problem of the writing’s body is one of the most important entrances to approach to the strokes of the poet-painter Henri Michaux. Thus, the present article proposes an unprecedented reflective look, alongside Jacques Derrida and Jean-Luc Nancy’s ideas that touches the writing itself. Accordingly, we analyze through the theoretical texts and works of the mentioned artist his beginning around the figurative body and how he passes to write the body itself with ideographic routes where the stroke as a preliteral writing (Derrida’s term) is exploited. In this sense, we propose a close reading of the graphic book Saisir as a paradigmatic case of the writing body’s research from the centrality that the touch holds in his work.